PETRARCHAN CONTEXTS OF JOHN DONNE’S SPIRITUAL LYRICS - Maryana V. Markova (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The article is devoted to the connection of the famous English poet, prose writer and preacher John Donne’s (1572–1631) works with the Petrarchan discourse of the European literature. The purpose of the investigation is to reveal and interpret the elements of Petrarchism in spiritual lyrics of the author on the basis of systematic approach with the use of the genealogical and comparative typological methods. The most prominent cases of the traditional Petrarchan themes, motives and images usage in John Donne’s religious texts and the specifity of their functioning have been examined in this article. Our attention has been paid to the genetic interconnection between the courtly rhetoric, which had been inherited by Francesco Petrarch and his numerous followers from the Provencal troubadours, and the traditions of the European mysticism that causes the harmony of the Petrarchan interpretive contexts according to the spiritual lyrics of the writer. Already in his earliest works, in particular in the book «Songs and Sonnets», John Donne did not avoid mixing the sacred and the profane, quite intensively using religious images and motifs in love poetry. But his Petrarchism is most notable in his «Holly Sonnets». The poetry of this cycle is not about God at all, but about the author himself in his relationship with Lord. In these sonnets the writer describes his feelings for God in almost the same way as Francesco Petrarch described his love for Laura. In general, if we talk about Petrarchism in relation to the spiritual lyrics of John Donne, it should be noted that for the writer it was not only a convenient source of the «ready» artistic images, motifs or means of expression but a kind of a perfect artistic technique for expressing secret, deeply personal thoughts and emotions. The conclusion has been done that such typically Petrarchan ideas such as: the dedicated service to the object of feelings, slavish adoration, obedience and dependence on its inconstant wishes John Donne has managed to adapt to the special needs of the sacred genres in such a way that his texts look surprisingly attractive, interesting and clear to different readers. Despite his worldwide fame John Donne is still one of the least researched literary figures in Ukrainian science. The article is directed to study only one of many aspects of his many-sided artistic heritage which needs the comprehensive professional analysis of the literary theorists and historians. So this article can be used for the further investigation of the problems, connected with the Petrarchan discourse generally in English literature and particularly in John Donne’s works and the scientific results proposed in it can be used in writing course works, graduation works and thesis on the related themes.